2016
DOI: 10.1177/1557988315599825
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Sugar-Sweetened Beverage Consumption Change Efficacy Among Male First-Year College Students

Abstract: Racial disparities in weight-related outcomes among males may be linked to differences in behavioral change efficacy; however, few studies have pursued this line of inquiry. The purpose of this study was to determine the degree to which self-efficacy associated with changing sugar-sweetened beverage (SSB) consumption intake varies by race among male first-year college students. A self-administered, cross-sectional survey was completed by a subsample of freshmen males (N = 203) at a medium-sized southern univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Recent studies conducted in college aged individuals reported implications for testing the differences in self-efficacy between males and females and also indicate possible racial differences in self-efficacy for improving certain health behaviors. A study published in 2015 by Bruce et al (25) reported significantly lower self-efficacy for changing sugar sweetened beverage consumption in African American college males compared to white college males. In addition, a study examining Korean college students reported that self-efficacy for physical activity is a significant predictor of physical activity in Korean males but not in Korean females.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies conducted in college aged individuals reported implications for testing the differences in self-efficacy between males and females and also indicate possible racial differences in self-efficacy for improving certain health behaviors. A study published in 2015 by Bruce et al (25) reported significantly lower self-efficacy for changing sugar sweetened beverage consumption in African American college males compared to white college males. In addition, a study examining Korean college students reported that self-efficacy for physical activity is a significant predictor of physical activity in Korean males but not in Korean females.…”
Section: Discussionmentioning
confidence: 99%
“…Among college-aged adults, studies have shown greater physical fitness and healthier diets among Caucasian students as compared to Black/AA students, 64 with a lower proportions of Black/AA males asserting confidence in their ability to change behaviors associated with sugar-sweetened beverage consumption. 65 Future research aiming to enhance protective health behaviors against chronic disease among Black/AAs should explore how to capitalize on these credible sources of health information to promote positive health indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing sugar consumption has been identified as weight management and chronic disease prevention strategy (Johnson et al, 2009; Kumanyika, Grier, Lancaster, & Lassiter, 2011; Kumar et al, 2014); however, replacing consumption of sugared beverages and snacks with healthier options could be salient for high risk groups like African Americans to help reduce the likelihood and impact of obesity and related chronic diseases. Behavior change is difficult; however, only one study to our knowledge has assessed the perceived degree of difficulty making lifestyle modifications among emerging adults (Bruce, Beech, Thorpe, & Griffith, 2015). The current study used data drawn from a sample of African American and White first-year college students to assess racial and gender disparities in SSB and sugary snack behavioral modification efficacy.…”
Section: Discussionmentioning
confidence: 99%